2020
DOI: 10.1371/journal.pone.0236623
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the narrow band imaging (NBI) in decision-making process regarding second look procedure (SL) in laryngeal cancer follow-up after transoral laser microsurgery

Abstract: Background The prognostic value of positive surgical margins after transoral laser microsurgery (TOLM) is still under debate. In case of positive superficial margins, some experts recommend a second-look surgery (SL) and some recommend wait and watch approach with close observation. Narrow band imaging (NBI) is an advanced imaging system used to enhance visualization of mucosal vascular pattern. In laryngology, NBI is used to improve the detection of premalignant, dysplastic and malignant lesions. Aim To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Distinct from intraoperative margin assessment, an interesting application for NBI is the follow-up of patients with early to moderate stage glottic cancer after curative treatment. Witkiewicz et al recently reported that NBI after TLM is a good predictor of margin positivity, supporting clinical decision-making regarding the need for second-look surgery [ 53 ]. NBI during outpatient transnasal endoscopy was found to be an excellent follow-up tool of laryngeal cancer patients after radiotherapy to screen for recurrent disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from intraoperative margin assessment, an interesting application for NBI is the follow-up of patients with early to moderate stage glottic cancer after curative treatment. Witkiewicz et al recently reported that NBI after TLM is a good predictor of margin positivity, supporting clinical decision-making regarding the need for second-look surgery [ 53 ]. NBI during outpatient transnasal endoscopy was found to be an excellent follow-up tool of laryngeal cancer patients after radiotherapy to screen for recurrent disease [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the morphology of the mucosal epithelium and the microvascular morphology of epithelial cells can enable us to better observe and evaluate the morphology of intraepithelial papillary capillary loop (IPCL) and detect some lesions that are difficult to find under ordinary white light endoscopy; this provides a new approach for the early detection of lesions with different properties and different degrees. 7 , 8 In recent years, NBI endoscopy has been gradually used for diagnosing laryngopharyngeal lesions. 9 Therefore, we compared the diagnostic results of vocal cord lesions examined by NBI endoscopy‐based IPCL classification with those of vocal cord lesions examined by the reference standard pathological test.…”
Section: Introductionmentioning
confidence: 99%
“…HPV plays a significant role in the pathogenesis of cancer of the oral pharynx. In contrast, the impact of oncogenic HPV infections (16,18,31,33,35) on the cancer transformation process in laryngeal malignancies appears to be much smaller and not fully understood. It is estimated that viral DNA incidence ranges from 20% to 30%, but this percentage varies among researchers and depends on the detection method applied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure can be performed as a diagnostic and during endoscopic laser cordectomy, as it allows a more precise assessment of the status of surgical margins of early-stage and locally advanced laryngeal cancers [16,17]. Narrow band imaging is also a practical tool in laryngeal cancer follow-up after surgical procedures such as transoral laser microsurgery or radiotherapy [18]. This diagnostic process is not always sufficient; however, it can be supplemented with direct laryngoscopy using the collection of samples for histopathological examination, usually performed under general endotracheal anesthesia in operating room conditions.…”
Section: Introductionmentioning
confidence: 99%